(untitled) (UNED Research Journal, 2017)
Tilapia is the second most important cultured species in the world fish culture but it can be affected by parasites. We conducted a cross-sectional parasitic study in tilapia larvae during sexual reversion for two seasons in Costa Rica. A total of 320 larvae from a concrete pond were necropsied and we found ten parasite species: Ichtyobodo sp., Apiosoma sp., Chillodonella sp., Heteropollaria sp., Trichodina sp., Dactylogyrus sp., Girodactylus sp., Centrocestus sp., lasidies and glochidies (two larval forms). These were classified in five taxonomic groups (two subtypes of protozoa, two metazoan classes and a type of mollusk). Protozoans and monogeneans (except Trichodina sp.) had a higher prevalence in the rainy season, when water had more solid waste, while digeneans and molluscs were more prevalent in the dry season, with different infection dynamics over gills, skin, fins and head.